THE PROFILE OF STUDENTS' CRITICAL THINKING THROUGH SCIENCE VIRTUAL TEST ON EIGHTH GRADE SECONDARY SCHOOL - Nurismawati, Riana (2017)
The purpose of this study is to describe the profile of students' critical thinking by using Science Virtual Test in three Junior high schools in Tasikmalaya city and to find out whether students' critical thinking has a correlation between science topic, science score achievement and students' logical thinking. The subject theme of this research is living things and environmental sustainability. The respondent consists of 168 students from eighth grade at three public schools inTasikmalaya city. Science Virtual Test, Test of Logical Thinking, Science score from science teacher and Students' impression questionnaire were used in this research study. Science virtual test instrument consist of 26 questions with 5 different topics. IBM SPSS 23.00 program was used for analysis of the data. This research method was using descriptive and correlational method. By the findings; overall students' critical thinking attainment reaches 63.1 percent which is categorized on moderate level means the students' are between in the stage of beginning thinkers and practicing thinkers. The students' attainment for each topic includes as moderate level. There is no correlation between students' critical thinking and science score achievement. There is positive and weak (0.187) correlation between students' critical thinking and students' logical thinking attainment. Students' impression from the result of questionnaire shows that is positive respond(3,55) or good impression after using Science Virtual Test. Keywords: Students' Critical Thinking Skill, Science Virtual Test, Penelitianinimemilikitujuanuntukmendeskripsikanprofilkemampuanberpikirkritisdenganmenggunakan Science Virtual Test di tiga SMP di kotaTasikmalayadanuntukmengetahuiapakahkemampuanberpikirkritissiswamemilikikorelasiantaratopiksains, pencapaiannilaisainsdankemampuanberpikirlogissiswa. Subjektemadalampenelitianiniadalahmakhlukhidupdankeberlanjutanlingkungan.Respondenterdiridari 168 siswakelas VIII di tigasekolahnegeri di kotaTasikmalaya. Science Virtual Test (SVT), Test of Logical Thinking (TOLT), NilaiIlmuPengetahuanAlamdari guru sainsdankuesionermengenai Science Virtual Testdigunakandalampenelitianini. Science Virtual Test terdiridari 26 pertanyaandengan 5 topikberbeda.Program IBM SPSS 23.00 digunakanuntukanalisis data.Metodepenelitianinimenggunakanmetodologideskriptifdankorelasi.Dengantemuan; Prestasiberpikirkritissiswasecarakeseluruhanmencapai 63.1 persen yang dikategorikanpadatingkatsedang yang berartisiswaberadadiantaratingkatanPemikirPemula (Beginning Thinkers) danPemikirPraktis (Practicing Thinkers).Prestasisiswauntuksetiaptopiktermasuktingkatmoderatatausedang.Tidakterdapatkorelasiantaraprestasiberpikirkritissiswadanprestasisains.Terdapatkorelasipositifdanlemah (0.187) antarapemikirankritissiswadanpencapaianpemikiranlogissiswa.Kesansiswahasildarikuisionermenunjukkanresponpositif(3.55) ataukesanbaiksetelahmenggunakan Science Virtual Test. Kata kunci: KemampuanBerpikirKritisSiwa, Science Virtual Test,